Effect of cutting conditions on surface roughness of machined parts in CO2 laser cutting of pure titanium. (2021) - Boujelbene, M.; El Aoud, B.; Bayraktar, E.; Elbadawi, I.; Chaudhry, I.; Khaliq, A.; Ayyaz, A.; Elleuch, Z.
Abstract: Titanium (Ti) and its alloys machining has been a long standing issue in the manufacturing industry. The extraordinary Ti machining costs restrict its used in the specialised applications. To achieve improved surface quality, researchers are working tirelessly to optimize various cutting parameters. In this study, high-power CO2 laser cutting of the 2 mm thick sheet of pure Ti is investigated. Additionally, effect of the input laser conditions on the machine surface quality is also analysed. The arithmetic roughness Ra and total roughness Rt of the cut work-pieces, produced by different cutting speed ( V ), laser power ( Pu ) and gas pressure ( p ) are measured by the roughness tester. The machined or cut surfaces were analyzed at several locations along the cutting surface. The Taguchi method was applied to minimize the surface roughness of the cut parts and to optimize the cutting parameters. It was observed that surfaces roughness increases with the evolution of the thermal energy by laser power. However, surface roughness decreases with faster cutting speeds. Finally, the optimum cutting conditions for the arithmetic roughness ( Ra ) was recorded at laser power Pu of 2 kW, V of 2400 mm/min and p of 14 bars. For total roughness (Rt), Pu, V and p were 2 kW, 2400 mm/min and 2 bars respectively.